Influence of Teams Games Tournament (TGT) Learning Model Assisted By Snakes and Ladders Media on Learning Outcomes - Oktaviona Sri Gunawan; Kori Sundari (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2025)
This research related to conditions at SD Negeri Teluk Pucung III, Bekasi City, especially unsatisfactory student learning outcomes and learning objectives that did not optimally achieved due to limited teaching methods. It is known from observations and discussions with students, teachers and guardians who stated that educators have limitations in delivering material so that it is less interesting and ineffective. This research aims to explore the use of TGT teaching method in learning achievement of fifth grade students. The method used is quantitative method that design pretest-posttest group with pre-experimental approach. Data collection techniques include observation, review and the use of pretest and posttest questions. Research population is grade V students at SD Negeri Teluk Pucung III, Bekasi City with sample of 30 VC class students. To evaluate data, techniques applied are parametric data analysis including validity tests, reliability tests and normality tests. The Sig value produced before treatment was 0.593 and test result after treatment was 0.068, where the results of two Sig values were >0.05 so that the data met criteria and could be continued with t-test. Results of the t-test are average score obtained for pretest is 22.17 while average score for posttest is 34.33. So, from results of data analysis, there is an increase in value of Pretest to Posttest. This shows the influence of TGT teaching method on student learning outcomes with an influence level of 90%.Keywords: Team Games Tournament, Media, Learning Outcomes, Elementary School.